Kesantunan Berbahasa Warganet dalam Podcast Deddy Corbuzier - Hardika Hutriana Putri; Ermanto Ermanto (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aimed to find the types of speech acts and politeness in the citizen's language found in Deddy Corbuzier's podcast. Data collection is done by the method is descriptive method. The data sources in this study are three video podcasts of Deddy Corbuzier. The data was taken from October to December 2021. The data collection technique used in this study was the free-to-talk and note-taking technique. Data analysis techniques in this study followed Miles and Huberman: data reduction, data presentation, and drawing conclusions. The results of the study are as follows. First, four types of speech acts were found, namely, 227 representative utterances, 76 directive utterances, 91 expressive utterances, and 6 commissive utterances. Second, there are six maxims of politeness in language, namely 44 utterances of wisdom, 3 utterances of generosity, 93 utterances of praise, 22 utterances of consensus, 29 utterances of simplicity, and 147 utterances of sympathy. Meanwhile, deviations from the politeness principle were found in six maxims, namely 11 utterances of wisdom, 1 utterance of generosity, 14 utterances of appreciation, 2 utterances of consensus, 6 utterances of simplicity, and 28 utterances of sympathy.